Predictive validity of lower extremity muscle strength, strength asymmetry, and soccer-specific fitness for talent identification in elite male youth soccer players: A retrospective cohort study - Hwang, S.; Kim, J.; Park, I. (Measurement in Physical Education and Exercise Science, 2024)
This study investigates the predictive validity of lower extremity strength, strength asymmetry, and soccer-specific fitness in talent identification among elite male youth soccer players. Employing a Retrospective Cohort design, we established a cohort consisting of K-League registered youth players, totaling 219 individuals (all males, aged 16 ~ 17 years, in grade 2 of high school; equivalent to grade 11 in the US), with 38 progressing to the professional level and 181 not. Results from t-tests revealed significant differences between professional and nonprofessional groups for countermovement jump (CMJ; t = -2.423, Cohen`s d = -.448, p = .019) and change of direction with a ball (CODB; t = 2.202, Cohen`s d = .398, p = .032). CMJ demonstrated a significant correlation with the 30 m sprint (r = -.53, p < .001), and change of direction without a ball (COD) correlated with CODB (r = .52, p < .001). The robust Poisson regression, encompassing the interaction term of COD and CODB, produced an AUC of .73 (95% CI: .65 ~ .82).